PENGARUH DRILL SHOOTING BOLA BERGERAK TERHADAP AKURASI SHOOTING DENGAN MENGGUNAKAN KAKI BAGIAN DALAM SISWA EKSTRAKURIKULER FUTSAL SMP NEGERI 1 KRAMATMULYA - Aksan Ibnu Firmansah Ibnu Firmansah (STKIP Muhammadiyah Kuningan, 2021)
This study aims to improve the drill shooting ability of moving balls with respect to accuracy using the inside of the foot in futsal extracurricular members of SMP N 1 Kramatmulya. This research is an experimental study which was carried out for approximately two months, with the intensity of meeting three times a week. In total there are 6 weeks with a frequency of exercise 3 times in 1 week. Data were collected through pretest and posttest. The data were analyzed using SPSS version 20. The results showed that the ball drill shooting method moved to accuracy using the inner foot of the futsal extracurricular members of SMP N 1 Kramatmulya